Tecnologias Digitais da Informação e Comunicação (TDIC's) no ensino de geografia em Uberaba MG - Santos, Enágio Fernandes dos (2023)
Teaching, currently, has taken new directions that lead us to reflect on the world we live in with regard to the current model of education and the challenges that arise in the school environment. We can observe that for the construction of a critical/reflective and conscientious thinking, it is necessary to have appreciation and effective participation of the State concerned with supporting new teaching practices. Thus, the present study aims to understand the process and contributions of the use of DICTs in the teaching of Geography by teachers of the state public education in Uberaba (MG) through the perception of these teachers regarding the influence of technologies in teaching and learning. This is a qualitative research with questionnaires applied to teachers from four state public schools. The selected target audience is represented by a sample of 8 teachers who answered the questionnaires between August and November 2022. For the analysis and interpretation of the data, the software for the organization of central ideas such as excel and word, and the technique of content analysis was used as possibility for analyzing the participants' reports. The results demonstrated through the report of the professors showed evidence of the potentialities of the DICTs and the use of some of them in the daily life of the teachers. However, few challenges translated into difficulties such as lack of knowledge due to lack of adequate training, followed by the infrastructure of schools, devaluation of professionals by public agencies, consequently the lack of interest of teachers and the clash with the model of traditional and descriptive teaching that still predominates in various practices, makes the adoption of new strategies even more complicated. This scenario was visible from the interviews that show the concern of educators with teaching and learning of their students and the initiative of the institution at all times to keep up to date with the theme, always keeping concerned with acquiring technological materials to assist in the acquisition of knowledge. Therefore, it is concluded that more than providing digital information and communication technologies to schools or stimulating their use, circumstances should be provided for teaching and learning to occur effectively. For geography, the use of technology allows us to manipulate maps and charts quickly, view them at different scales, and highlight different features, providing a very powerful learning environment by allowing greater autonomy in geographic queries with access to web based information and data manipulation and presentation tools. It is necessary to invest in teacher training so that educators can use the equipment and technological resources for the benefit of education and pedagogical purposes. In this logic, it becomes indispensable, for the achievement of quality education, to expand investment in an uninterrupted and long term way. In addition, the imprescindibility of tracing new paths in the teaching and learning process, compatible with the knowledge of today.